Competence, Work Discipline, and Work Facilities Contribute to Improving Employee Performance - Dieva, Diknastiya Putri; Swasti, Ika Korika (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
In the increasingly modern era of globalization, companies must compete fiercely to maintain their existence and achieve success. The realization of success is certainly not without various challenges, one of which relates to employee performance. This is often influenced by competence, work discipline, and workplace facilities. This research aims to determine the influence of competence, work discipline, and work facilities on the performance of production employees at PT. Romi Violeta Sidoarjo. The population and sample consisted of 38 employees. Data collection was conducted through a questionnaire, which was then processed using SmartPLS. The results indicate that competence, work discipline, and work facilities have a positive effect on employee performance. The higher the competence of the employees, the better their performance. Furthermore, the greater the discipline applied by employees, the higher their performance will be. Similarly, the more available and adequate the work facilities are to support their tasks, the faster the performance process will be.